The Kids' nature book 365 indoor/outdoor activities and experiences - Milord, Susan (Charlotte, VT Williamson Pub., 1989)
Suggests activities, poems, and stories to explore nature throughout the year.
Keywords: Nature study -- Juvenile literature; Natural history -- Outdoor books -- Juvenile literature; Natural history -- Outdoor books; Nature study